EFFICIENCY OF SOIL WASHING IN REMOVING PETROLEUM HYDROCARBON RESIDUES - Rasyidan Rizqi Ramadhan; Harmin Sulistiyaning Titah; Nur ’Izzati Ismail (Department of Environmental Engineering-Faculty of Civil, Planning, and Geo Engineering. Institut Teknologi Sepuluh Nopember, Surabaya, 2026)
Soil contamination by petroleum hydrocarbon residues, particularly from used motor oil, requires effective and relatively simple remediation technology. This study evaluated the efficiency of pilot-scale soil washing using the non-ionic surfactant Polysorbate 80 to remove Total Petroleum Hydrocarbon (TPH) from artificially contaminated sandy soil. The contaminated medium was prepared by mixing commercial sand and used motor oil at a ratio of 85:15, resulting in an initial TPH concentration of 13.5039% or 135,039.42 mg/kg. Pilot-scale batch soil washing was conducted using a drum rotary agitator at 50 rpm with variations in Polysorbate 80 concentration (0.5%, 1.5%, and 2.5%), washing time (30, 60, and 90 min), and solid/liquid ratio (1:5, 1:10, and 1:15). TPH was analyzed using a gravimetric method, and the removal efficiency was calculated based on the difference between the initial and final concentrations. The results showed that soil washing removed TPH with efficiencies ranging from 68.72% to 92.40%. The highest efficiency of 92.40% was achieved at 1.5% Polysorbate 80, a 60 min washing time, and a 1:10 solid/liquid ratio. A low surfactant concentration of 0.5% also produced a high removal efficiency, reaching 89.66% at 30 min and a 1:10 ratio. In contrast, a 2.5% surfactant concentration combined with a short washing time produced the lowest efficiency, presumably due to stable emulsion formation and mass-transfer limitations. These findings indicate that pilot-scale soil washing with Polysorbate 80 is effective in removing TPH from sandy soils, particularly under low-to-moderate surfactant concentrations and a 30–60 min contact time.